2013
DOI: 10.3748/wjg.v19.i41.7146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel auto-fluorescence imaging system with computer-assisted color analysis for assessment of colorectal lesions

Abstract: The novel AFI system with color analysis was effective in distinguishing non-neoplastic lesions from neoplastic lesions and might allow determination of the depth of invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Inomata et al demonstrated that quantitative analysis of the AFI color using the G/R ratio was effective in distinguishing sporadic neoplastic lesions (28). The most important observation in the present study is that we found for the first time that the G/R ratio is helpful in discriminating dysplasia/cancer in UC as well.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Inomata et al demonstrated that quantitative analysis of the AFI color using the G/R ratio was effective in distinguishing sporadic neoplastic lesions (28). The most important observation in the present study is that we found for the first time that the G/R ratio is helpful in discriminating dysplasia/cancer in UC as well.…”
Section: Discussionsupporting
confidence: 69%
“…The color of mucosa was divided into green as non-neoplastic or purple as neoplastic. due to individual variations in the AFI intensity, the AFI intensity of any identified lesion was also compared with the intensity of the non-neoplastic area (both UC-involved and -uninvolved area) in each individual, and the corrected value, termed green/red (G/R) ratio, was estimated by dividing the green color tone intensity values by the red color tone intensity values, based on the method previously reported (28). Color tone intensity analysis was carried out with still images of the colorectal Histopathology.…”
Section: Conventional Endoscopic Analysismentioning
confidence: 99%
“…Amongst the device improvements, the following should be highlighted: 1) increase in image resolution and, consequently, textural information; 2) the use of wide-angle cameras showing more colon wall surface; 3) the development of zooming and magnification techniques [15] and 4) the development of new imaging methodologies such as autofluorescence imaging [16] or virtual chromoendoscopy (Olympus' Narrow Band Imaging [17], Fujinon's FICE [18] or Pentax's i-Scan [19]). This last group of techniques modify how the scene is observed by improving the contrast of endoluminal scene elements, which may help in lesion detection and also with in-vivo lesion diagnosis due to the enhanced visualization of lesion tissues [20].…”
Section: B Technical Strategies To Improve Polyp Detection Ratementioning
confidence: 99%
“…AFI provides a green/red image that can be analyzed by a computer algorithm . Japanese medical groups conducted experimental research based on prototype software that calculates the green/red ratio of the acquired image and evaluated its performance prospectively. (See the section Prospective study with in vivo use of AI. )…”
Section: Automated Polyp Characterizationmentioning
confidence: 99%